Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5713/ajas.20.0238
|View full text |Cite
|
Sign up to set email alerts
|

TATA box binding protein and ribosomal protein 4 are suitable reference genes for normalization during quantitative polymerase chain reaction study in bovine mesenchymal stem cells

Abstract: Objective: Quantitative polymerase chain reaction (qPCR) has been extensively used in the field of mesenchymal stem cell (MSC) research to elucidate their characteristics and clinical potential by normalization of target genes against reference genes (RGs), which are believed to be stably expressed irrespective of various experimental conditions. However, the expression of RGs is also variable depending on the experimental conditions, which may lead to false or contradictory conclusions upon normalization. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…It has been shown that RPS15A and RPS9 were the most stable internal reference genes in the Indian buffalo and bovine peripheral blood mononuclear cells 7 . RPL15 was also the most stable internal reference in bovine oocytes collected in winter and summer 28 , while RPL4 was the most stable internal reference gene in bovine bone marrow mesenchymal stem cell differentiation 32 . RPS9 and RPL19 in bovine maternal reproductive tissues and fetal tissues were found to be stably expressed 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that RPS15A and RPS9 were the most stable internal reference genes in the Indian buffalo and bovine peripheral blood mononuclear cells 7 . RPL15 was also the most stable internal reference in bovine oocytes collected in winter and summer 28 , while RPL4 was the most stable internal reference gene in bovine bone marrow mesenchymal stem cell differentiation 32 . RPS9 and RPL19 in bovine maternal reproductive tissues and fetal tissues were found to be stably expressed 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that the discrepancy in the ranking of the reference gene was caused by differences in the experimental condition. Hence, before analyzing gene expression by qRT-PCR, selection of the most stable reference gene under particular experimental conditions is an essential step [ 22 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Bestkeeper index was compared in a pair-wise fashion via Pearson correlation coefficients for evaluating the reference gene stability ranking [ 24 ]. Previously, we analyzed the most stable reference gene in other species using three algorithms [ 21 , 22 , 25 ]. Eight candidate reference genes were estimated by independent statistical algorithms, different stability ranking was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Specific primers for the selected genes ( Table 2 ) were designed de novo through the Primer-BLAST and AutoDimer online applications [ 29 , 30 ]. TATA-box binding protein (TBP) gene, which is constitutively expressed, was used as a control to normalize the results [ 31 ]. The gene expression units are expressed as relative quantities of mRNA.…”
Section: Methodsmentioning
confidence: 99%